Holy Horror: Medicine, Martyrs, and the Photographic Image 1860–1910. Issue 24 (12th May 2017) - Warren, Treena
Using examples from the archives of Barts Pathology Museum in London, this article identifies and explores a trend in early medical photographs for adopting the visual codes of religious imagery, particularly depictions of martyred saints. Although the medical photograph emerged under the auspices of the empirical study of the body, it was decidedly different in its approach and appearance to the anatomical illustration of the nineteenth century, which in its quest for scientific objectivity had developed a fragmented and literal appearance that represented the body as isolated parts. In contrast, the Victorian medical photograph often portrayed entire persons, aligning it more closely with traditions of portraiture and figurative painting, and opening a space for the contemplation of the damaged body in aesthetic, moral, and spiritual, as well as practical terms. As the dominant icon of corporal suffering in Judaeo-Christian-influenced Western cultures, the figure of the martyr in painting and ecclesiastical imagery provided a model for the medical photograph's artistic interpretation of the body in abject states of illness, injury, and death. Invoking the martyr — whose physical agony is the catalyst to his or her mystical transcendence — legitimated the viewing of such body horror as religious edification and contextualized the experience of pain as an ennobling and spiritually rewarding experience. The article argues that in drawing on these diverse influences, the medical photograph presented a return to the integrated study of the body seen in the early modern illustrated anatomy: a genre of book which combined information on human physiognomy with aesthetic expression and emotional and moral meditations on the meaning of mortality and the nature of the Divine.